Debating imaginal politics dialogues with Chiara Bottici - Adams, Suzi; Smith, Jeremy, 1966- (Social imaginaries., 2022)
"A critical appraisal of Chiara Bottici's influential work on imaginal politics, this collection uses this rich theoretical framework for incisive analysis, within critical theory and political philosophy, psychoanalysis and sociology"--